PENERAPAN WILLIAM FLEXION EXERCISE PADA KASUS NYERI PUNGGUNG BAWAH (LOW BACK PAIN) - Widarti, Rini (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Indonesia is one of the developing countries in the world, it is shown by the increasing number of industries that grow from time to time. Solo Baru is one of the areas in the city of Sukoharjo which recently experienced a very rapid growth. The modern lifestyle adopted by the majority of Indonesian society makes it possible for a disorder of work-related diseases such as routine activities in the printing book of Ar Risalah Cipta Media ?like a sitting position, long standing and excessive activities with a non-ergonomic position to the factor of back pain or better known as low back pain, this can be a serious problem if you do not get the right services and counseling. Method of Implementation: lectures and demontration. Conclusion: the employees at the printing book Ar Risalah Cipta Media? understand the procedure of treating lower back pain and understand the bad effect if lower back pain is not handled properly which will have an impact on body productivity in work.?